Pengaruh Penggunaan Model Kooperatif Tipe STAD terhadap Hasil Belajar PAI di SDN 16 Kota Padang - Asri Sauci Ramadhani; Alfurqan Alfurqan (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
This study aims to determine the effect of the use of cooperative learning model type Student Team Achievement Divisions (STAD) on student learning outcomes in PAI subjects in class III SDN 16 Tanjung Aur, Padang City. This type of research is quantitative research with experimental methods. The research design is a one-group pretest posttest design. This research was conducted at SDN 16 Tanjung Aur, Padang City. The sample of this research is class III B students, totaling 28 people. Collecting data in this study is a test. The data obtained were analyzed using the t-test (t-test). The results of this study obtained an average pretest value of 61.54 (before using the STAD cooperative model) and an average posttest value of 80.39 (after using the STAD cooperative model). Based on the calculation of the t-test obtained tcount = 16,176 and the value of sig. of 0.000. Thus that the value of sig. 0.000 <0.05, it means that there is a significant effect of using the STAD type cooperative learning model on student learning outcomes in PAI subjects in class III SDN 16 Tanjung Aur, Padang City.